EVALUASI PENERAPAN SIMRS DI RUMAH SAKIT PUTRA WASPADA DENGAN METODE HOT-FIT - Ana Fitriani; Fita Rusdian Ikawati; Achmad Jaelani Rusdi (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2023)
The implementation of SIMRS is very important to work together on all information generated in the health service process. SIMRS can also encourage increased efficiency and effectiveness of services in hospitals in line with the smooth flow of information from hospital operational activities. To support this, the application of SIMRS must be in accordance with the needs of each room so that it can run well. The purpose of this research is to find out how the Hot-Fit method affects the implementation of SIMRS. This research is a quantitative research. The research variables are System Quality, Information Quality, Service Quality, System Use, Use Satiaction, Structure, Net Benefit, the sample is SIMRS users. The success of SIMRS implementation at Putra Waspada Hospital is influenced by human, organizational, technological aspects, and the benefits of having a positive influence.